Unpacking land-associated assemblages 'from below': Smallholders' land access strategies at the commercial tree-crop frontier. (January 2023) - Van Leynseele, Yves; Olofsson, Malin
Abstract: Market-oriented agrarian transformation challenges notions of the 'communal' nature of customary land. This paper foregrounds the emergent patterns of land access in the context of an expanding tree-crop commodity frontier in the former 'homeland' of Venda, South Africa. We develop an actor-focused, assemblage approach and use it to identify how three entrepreneurial, accumulating tree-crop farmers engaging in commercial macadamia nut and avocado production mediate land access through a combination of historic access, social networks, insider-knowledge, access to capital and brokering of good community relations through land sharing and job provisioning. We approach this mediation as (re)-assembling practices that unfold within the particular conditions at this historical conjuncture and the gradual agricultural de-activation in food crop production and urbanisation occurring locally. These practices blend collective and private elements into an unwieldy, land-associated assemblage in ways that challenge the political economical reading of the commoditisation trend as a 'the single land grab', 'accumulation from below' or as leading to the neoliberalisation of African land tenure systems. We argue that this reconstruction 'from below' requires attention to the way situated practices forge relations to other (translocal)assemblages, local agency in shaping land- and production relations, the opportunity structure related to changes in the local political economy and a sensibility to the multiple, possible futures of this frontier moment.